1986
DOI: 10.1088/0034-4885/49/5/001
|View full text |Cite
|
Sign up to set email alerts
|

Materials modification with ion beams

Abstract: The incorporation of impurities into solids by bombardment with energetic ions is a non-equilibrium process which can result in intriguing near-surface property changes. This review initially examines the basic ion-solid interaction processes and outlines how such processes can lead to the modification of the composition, structure and surface topography of materials. Ion implantation has been exploited in widely diverse fields both as a powerful research tool for investigating solid state material processes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(49 citation statements)
references
References 326 publications
1
48
0
Order By: Relevance
“…2 ) . Probably, this effect is due to the formation of larger agglomerates of point defects or of extended defects like voids and dislocations as they have been found in helium implanted It is interesting to note that recently reported results for the fluence dependence of the microhardness in ion implanted silicon, sapphire and some other materials (B[JRNETT, BRIGGS; BURNIWT, PAGE 1984a, b, 1985, 1986H I O K~ et al) confirm our measurements. In these investigations it has been found that the microhardness increases with the ion fluence a t low fluences, then goes through a masimum a t some critical fluence and decreases a t higher fluences.…”
Section: Resultssupporting
confidence: 88%
“…2 ) . Probably, this effect is due to the formation of larger agglomerates of point defects or of extended defects like voids and dislocations as they have been found in helium implanted It is interesting to note that recently reported results for the fluence dependence of the microhardness in ion implanted silicon, sapphire and some other materials (B[JRNETT, BRIGGS; BURNIWT, PAGE 1984a, b, 1985, 1986H I O K~ et al) confirm our measurements. In these investigations it has been found that the microhardness increases with the ion fluence a t low fluences, then goes through a masimum a t some critical fluence and decreases a t higher fluences.…”
Section: Resultssupporting
confidence: 88%
“…This is not surprising since the melting point of GaN is very high ͑2518°C͒ and the removal of crystalline defects from other compound semiconductors normally requires temperatures in excess of two thirds of the melting point ͑in K͒. 8 What is surprising is that reasonable electrical activity can be obtained in GaN with so much residual damage. In this regard, the atom location measurements are illuminating since they suggest that Te is substitutional despite the disorder.…”
Section: Fig 2 Xtem Micrographs Showing the Structure For A Dose Ofmentioning
confidence: 99%
“…7 In other compound semiconductors such as GaAs and InP, implantation results in extensive crystalline damage and even amorphous layers which recrystallise epitaxially during annealing up to 400°C. 8 However, in both preamorphous and amorphous cases, low temperature annealing leaves a highly defective crystal which must be annealed at considerably higher temperatures ͑up to 900°C͒ to fully remove all defects and activate dopants. [8][9][10] In GaN, recent studies [11][12][13][14] have indicated that activation of both n-and p-type dopants can be achieved by annealing up to 1100°C but results are variable and the electrical properties are far from optimum.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An energetic ion loses its energy during its passage through material mainly by electronic energy loss (inelastic collision) and nuclear energy loss (elastic scattering). The nature of modification depends upon the electrical, thermal and structural properties of the target material, mass of projectile ion and irradiation parameter [12]. Impedance spectroscopy is a powerful technique for the study of ion transport processes [13].…”
Section: Introductionmentioning
confidence: 99%